Consumption of Canola Oil vs. Other Common Oil(s) in Dyslipidemia Management among Urban Indian Adults - Chauhan, Shraddha; Aeri, Bani (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
The present study was conducted to determine the effect of consuming canola oil vs. other common oil(s) on the lipid profile and anthropometric parameters of dyslipidemic adults. Eighty urban affluent dyslipidemic adults (40 experimental, 40 control) of age 30–45 years were enrolled from hospital based preventive health check programs for a 16-week non-randomized intervention trial. Dietary and lifestyle modification advice for management of lipid levels was provided to both the groups. Canola oil was provided for routine consumption only to the experimental group whilst the control group was advised to consume their usual oil(s) in recommended amounts (15ml/day). Height, weight, Body Mass Index (BMI), waist circumference (WC), Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL), Total Cholesterol (TC) and Triglycerides (TG) were measured at the beginning of the study (0 weeks), post run-in period (4 weeks) and post intervention period (12 weeks). Self-reported checklist was used to measure monthly compliance. Mixed effect linear regression and quantile linear mixed models were used to analyze the change in the parameters over time. There was no significant difference in the compliance towards dietary and lifestyle advice between both the groups (p=0.525; 0.795). The difference of changes in the lipid profile and anthropometric measurements between the groups observed over time was not statistically significant (Weight: p=0.206, BMI: p=0.553, WC=0.40, TC: p=0.505, TG: p=0.167, LDL: p=0.271, HDL: p=0.504). Hence, there was no difference in the effects of consuming canola oil vs. other common oil(s) in managing dyslipidemia. Similar beneficial changes were observed with consumption of both canola as well as other common oil(s).